CircHADHA-augmented autophagy suppresses tumor growth of colon cancer by regulating autophagy-related gene via miR-361 - Shi, Ying; Li, Jinying; Tang, Ming; Liu, Jingwen; Zhong, Yalu; Huang, Wei (Frontiers in Oncology, 2022)
Colon cancer undergoes a traditional pathway from colon polyps to colon cancer. It is of great significance to investigate the key molecules involved in carcinogenesis from polyps to malignancies. Circular RNAs (circRNAs) stably express in human body fluids such as plasma. Here, we demonstrated a differential expression patten of plasma circRNAs in healthy individuals, asymptomatic polyp and colon cancer patients using circRNA Arraystar microarray. We explored that circHADHA was upregulated in plasma from polyp patients, whereas downregulated in plasma from colon cancer patients. Overexpression of circHADHA promoted autophagy in colon epithelial cells. Moreover, in colon cancer cells, overexpression of circHADHA promoted autophagy, whereas inhibited cell proliferation and colony formation. CircHADHA increased the expression of ATG13 via miR-361 in both colon epithelial and cancer cells. ATG13 knockdown reduced autophagy even in the presence of circHADHA in colon cancer cells. Further, the growth of circHADHA overexpressing colon cancer cell-derived xenograft tumors was significantly decreased compared with control tumors in nude mice. In conclusion, circHADHA differentially expressed in plasma of healthy individuals, colon polyp and colon cancer patients. CircHADHA promoted autophagy by regulating ATG13 via miR-361 in both colon epithelial and cancer cells. CircHADHA suppressed tumor growth by inducing cell autophagy in colon cancer cells. CircHADHA acts as a non-invasive biomarker for auxiliary screening of precursor colon cancer and potential therapeutics for colon cancer treatment.